T-box transcription factor TBX1, targeted by microRNA-6727-5p, inhibits cell growth and enhances cisplatin chemosensitivity of cervical cancer cells through AKT and MAPK pathways. Issue 1 (1st January 2021) - Liu, Haixia; Song, Mei; Sun, Xiaoyan; Zhang, Xin; Miao, Huayan; Wang, Yankui
ABSTRACT: Cervical cancer (CC) is the fourth most common cancers among women worldwide. T-box transcription factor 1 (TBX1), a member of the T-box family, has anti-tumor effects in some types of cancer, but its role in CC is yet unknown. The aim of this study is to investigate the functions and underlying mechanisms of TBX1 in CC. Online database UALCAN showed that TBX1 was down-regulated in CC tissues compared with normal tissues and patients with lower TBX1 expression level had a poor prognosis. TBX1 overexpression significantly decreased the proliferation, migration, and invasion of Hela and SiHa cells. Conversely, cell apoptosis and chemosensitivity to cisplatin were promoted in TBX1-overexpressing CC cells. Moreover, up-regulation of TBX1 inhibited both AKT and MAPK signaling pathways. Furthermore, dual luciferase report assay indicated that TBX1 could directly bind to miR-6727-5p. In addition, TBX1 expression was inhibited by miR-6727-5p mimic and up-regulated by miR-6727-5p inhibitor. Knockdown of TBX1 reversed the inhibitory effect of the miR-6727-5p inhibitor on CC cells. This study demonstrates that TBX1, a target gene of miR-6727-5p, acts as a tumor suppressor in CC, indicating that TBX1 may be a new target for CC therapy. ABSTRACT: uf0001